False spider mites of the genus Pentamerismus McGregor (Acari: Tenuipalpidae) from Iran - Khanjani, Mohammad; Gotoh, Tetsuo (Zootaxa, 2008)
One known species of the false spider mite genus Pentamerismus, P. judicious De Leon is redescribed. Two new species, P. ueckermanni sp. nov. and P. behsharicus sp. nov. are described and figured based on females collected from Juniperus polycarpus L. leaves, Mazandaran province, Iran. A key to all known species of this genus is given.